The role of the school in tackling the exclusion of students within the framework of inclusive education: a perspective from critical realism (Polifonia, 2016)
for theorising the contested relationship between the school vs. society in tackling the exclusion of students, within the framework of inclusive education. Data collected through semi-structured interviews with teachers, as part of a PhD thesis, are used to examine if the school is an open or closed system and how this affects the exclusion of students. In particular, teachers’ views, working at two highly diverse schools in Cyprus, are used, to shed light on the relationship between students’ disadvantage, in terms of their immigrant and low socio-economic background, and their exclusion, in terms of their academic achievement at the school. Further, teachers’ views are used to examine if through its functioning the school responds to students’ disadvantaged circumstances. This research suggests that the school cannot tackle students’ exclusion because, even though it is an open system, it operates as a closed system.Keywords: Open and closed systems, inclusive education, poor ethnic minority students